Water Availability in Snow Dominated Regions under Projected Climatic Variability: A Case Study of Alpine Catchment, Austria - Laghari, A. N.; Soomro, M. A.; Siyal, Z. A.; Sandilo, S. H.; Soomro, T. A. (Engineering, Technology & Applied Science Research, 2018)
This study analyzes the response of various hydrological parameters and future water availability against anticipated climate variations in snow dominated alpine catchment in Austria. The parameters assessed are base flow, environmental flow, total flow, evapotranspiration, and snow cover duration. The distributed hydrological modeling system PREVAH is developed to assess the impacts through the combination of various climate change scenarios produced under the framework of the European project PRUDENCE. The model results clearly indicate an apparent shift from observed trends in monthly, seasonal and annual values. The mean annual changes observed by all model scenarios range between 45% to 60% decrease in snow cover duration, 15% to 20% increase in evapotranspiration, 5% to 15% decrease in base flow, and 15% to 25% decrease in total runoff values. However, mean annual changes observed in available water are marginal, just ranging from -3% to +2%. All regional model projections show more or less the same identical pattern of changes in analyzed parameters.